THE USE OF CARD GAME AND TOTAL PHYSICAL RESPONSE (TPR) METHOD TO IMPROVE DEAF STUDENTS’ ENGLISH ACHIEVEMENT AT SLB-B PERTIWI PONOROGO - Pratiwi, Septian Eka; Rochmahwati, Pryla (Institut Agama Islam Negeri Ponorogo, 2021)
Deaf students are having challenge in understanding language especially English language as third language. The difficulty of the students is to understand new vocabulary without the visual media. Besides that, the teacher seldom uses sign language and approaches to every student in teaching-learning process. In order to make students easily in learning English language, Some possible ways should be applied by using card game and one of method by using total physical response (TPR) method. Card game is a tool applied in learning process which helps student to remember new vocabulary by using picture and total physical response (TPR) is teaching method that can be applied to practice student motor activity. This research aimed to improve deaf students’ achievement by using card game and total physical response (TPR) on eleventh grade at SLB Pertiwi Ponorogo. In this research, researcher formulated the problems are: 1) How can card game and total physical response (TPR) improve student’s activeness in English class at SLB Pertiwi Ponorogo?. 2) How can card game and total physical response (TPR) method improve deaf students’ achievement at SLB Pertiwi Ponorogo?. The design of this research was classroom action research. It included two cycles to enrich deaf student English achievement. Each cycle covered four steps: planning, acting, observing and reflecting. The data were collected by observation, interview and documentation and vocabulary test.The result of the research showed that the students improve their achievement in two cycles. Students’ activeness improve significantly at 33,33% to 83,33% at the second cycle. Furthermore, there is improvement at students’ vocabulary mastery 66,67 % first cycle to 100% at second cycle.Based on result of the research, it can be concluded that the implementation of card game and total physical response (TPR) method can improve student’s English achievement.